Directed high-entropy doped high-nickel cobalt-free positive electrode material and preparation method thereof, and lithium-ion battery
The preparation of high nickel cobalt-free cathode materials through directional high entropy doping and spray drying methods solves the balance problem between the cyclic stability and discharge specific capacity of existing materials, achieves high energy density and long cycle stability, and simplifies the preparation process and reduces the environmental impact.
Patent Information
- Application Number
- CN202411018119.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-07-26
AI Technical Summary
When the existing high-nickel cobalt-free cathode materials improve cycle stability, the discharge specific capacity is low and cannot meet the requirements of high energy density. At the same time, traditional preparation processes have challenges such as long production cycles and great environmental impact.
Directed high-entropy doping strategy is adopted to dopant specific elements in the core and shell of high nickel cobalt-free cathode material, forming a high-entropy structure with high Li+ diffusion rate and external high lattice stability, and preparing by one-step mixed lithium combined with spray drying.
It achieves high discharge specific capacity and long cycle stability, solves the Li+ diffusion problem of the positive electrode material in the high deliquency state, and simplifies the preparation process and reduces the environmental impact.
Smart Images

Figure CN118983404B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy technology, and specifically relates to a directional high-entropy doped high-nickel cobalt-free positive electrode material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Energy is a key driving force for the development of modern society. As people's pursuit of sustainable development continues to intensify, the energy sector is also facing new challenges and opportunities. Globally, people are gradually realizing the limited nature of traditional energy resources and their adverse effects on the environment, so turning to renewable energy has become an inevitable trend. Clean energy such as wind power, solar energy, and geothermal energy has gradually become mainstream, and the innovation and improvement of energy storage technology has also attracted much attention. In the pursuit of energy security and environmental sustainability, humans are constantly exploring new forms of energy and efficient ways of utilization to achieve stability and environmental friendliness in energy supply.
[0003] As an innovative mobile energy storage device, lithium-ion batteries show the prospect of wide application in many fields such as fixed energy storage, smart grids, electric transportation and power vehicles. Its long cycle stability and excellent rate performance are crucial in achieving fast charging and high power output. These characteristics are not only crucial to increasing the service life and stability of the battery, but also of great significance to meeting today's growing energy needs and promoting the development of clean energy technologies. With the continuous advancement and innovation of science and technology, the performance and efficiency of lithium-ion batteries will continue to improve, bringing more possibilities for applications in various fields and promoting the entire energy industry to develop in a more sustainable and efficient direction. Looking at the current situation, if you want to achieve an energy density of more than 350Wh / kg, the high-nickel ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.8 Co 0.15 Al 0.05 O2 (NCA) becomes an inevitable choice, among which Co as one of the main components has the following main functions: ① inhibiting Li / Ni mixing; ② providing partial capacity; ③ improving rate performance and conductivity. However, Co is very unevenly distributed around the world, and there are problems such as high prices, which limits the further development of high-nickel ternary positive electrode materials. In response to this, researchers have developed a series of high-nickel, low-Co or Co-free positive electrode materials, but it is still impossible to balance the relationship between discharge specific capacity, rate performance and long-cycle stability.
[0004] In order to compensate for the effect of Co, the modification research mainly focuses on metal element doping (Me) and coating. On the one hand, inside the lattice, through the strong Me-O bonding and the columnar layer effect of the Li site, the layered oxygen framework is maintained while ensuring the rapid deintercalation of Li; on the other hand, on the lattice surface, the highly reactive Ni 4+ It has serious side reactions with the electrolyte to produce gas and prevent the release of lattice oxygen in a high-charge state. In addition, some emerging structural engineering, such as concentration gradient, core-shell structure, axially oriented grains and other modification measures can also be used to compensate for the problems caused by the reduction of Co or indeed, but the above measures still have the disadvantages of complex process and single optimization.
[0005] The concept of "high entropy" originally came from alloys. In recent years, this concept has gradually been introduced into oxides. The research on introducing high entropy strategy into high-nickel cobalt-free cathode materials is in its infancy. The high-nickel cobalt-free cathode materials modified by high entropy strategy still have some defects. For example, the prior art CN1 16632186A performs high entropy doping on the outermost layer of nickel-based cathode materials to form a gradient nickel-based cathode material with decreasing entropy from the outside to the inside. This method can improve the cycle life of nickel-based cathode materials to a certain extent. However, since it does not achieve full structural high entropy and the element selection is not optimized, the nickel-based cathode material does not maintain a high discharge specific capacity while improving the cycle stability. The discharge specific capacity of the cathode material is low (0.1C, the discharge specific capacity is 191.2mAh g -1 ), which cannot meet the requirements for high energy density. The prior art CN117059795A discloses a high-entropy alloy-modified high-nickel cobalt-free positive electrode material and a preparation method thereof, which can make the structure of the high-nickel cobalt-free positive electrode material relatively stable to a certain extent, and increase the near-surface migration rate of lithium ions; however, although this method realizes full-structure high-entropy doping, its doping strategy is not targeted, and the same doping scheme is used for the entire positive electrode material, which cannot improve the internal Li + It can be seen that providing a more optimized high-entropy doping strategy to improve the electrochemical performance of cathode materials is of great significance for promoting the practical application of high-nickel cobalt-free cathode materials.
[0006] In addition, in actual production, while ensuring the high quality of the positive electrode material, its preparation process is simple and efficient, which is also the goal to be pursued. Traditional methods for preparing high-nickel ternary positive electrode materials include high-temperature solid-phase method, sol-gel method, co-precipitation method and hydrothermal method. The high-temperature solid-phase method is simple and easy, but the material mixing is uneven, resulting in inhomogeneous positive electrode materials. The sol-gel method can achieve atomic-level mixing, but the processing cycle is long and it is difficult to produce commercially. The co-precipitation method is one of the widely studied methods, which can prepare high-performance materials, but there are problems of uneven element distribution and environmental pollution. It can be seen that the traditional method has challenges such as long production cycle and large environmental impact, and a new preparation process that is efficient, clean and controllable is needed to solve these problems. Summary of the invention
[0007] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:
[0008] One of the purposes of the present invention is to provide a directional high entropy doped high nickel cobalt-free positive electrode material, the directional high entropy doped high nickel cobalt-free positive electrode material comprises a core and a shell layer covering the core, the chemical formula of the high nickel cobalt-free positive electrode material is LiNi a B b C c D d O2, 0.6≤a≤0.99, 0.01≤b≤0.4, 0.01≤c≤0.2, 0.01≤d≤0.2, a+b+c+d=1;
[0009] Among them, B includes at least one element of manganese and aluminum; C is a doping element distributed in the core and is selected from elements other than Li in the first main group and the second main group in the periodic table; D is a doping element distributed in the shell and is selected from elements other than Li, Ni, Mn, Al and C in the second to sixth periods in the periodic table; the total number of element types of C and D doping elements in the directional high-entropy doped high-nickel cobalt-free positive electrode material is more than four, and the molar ratio of any two of the C elements and the D elements is 1-1.04:1-1.04.
[0010] The directional high entropy doping described in the present invention refers to the element doping of the Li site and the Me site of the high-nickel cobalt-free positive electrode material, and the total element types of the C and D doping elements are four or more, and the doping content is equal proportion or nearly equal proportion doping. Nearly equal proportion doping means that the molar ratio of any two of the C element and the D element is 1-1.04:1-1.04. In some embodiments, the directional high entropy doping is carried out while ensuring the high discharge specific capacity of the high-nickel (Ni>0.6) positive electrode material.
[0011] The C element replaces part of the Li sites in the core of the positive electrode material, and the D element replaces part of the Me sites in the shell of the positive electrode material.
[0012] The present invention solves the problem of poor stability and low conductivity of lithium-ion batteries formed by Co-free positive electrode materials on the basis of ensuring high entropy doping of the whole structure of high-nickel cobalt-free positive electrode materials. Specifically, the present invention performs targeted doping of specific elements (C elements) on the Li sites (3a sites) inside the positive electrode material particles to expand the Li + diffusion channel, improving Li + At the same time, the characteristic element (D element) is doped in a directional manner at the Me site (3b site) on the surface of the positive electrode material particles to stabilize the oxygen lattice and reduce the irreversible phase change by stabilizing the Me-O bonding bond; thereby obtaining an internal high entropy region with high Li + The positive electrode material is dominated by diffusion, while the external high entropy region is dominated by lattice stability, which solves the problem of Li + Slow diffusion and highly reactive Ni on particle surface 4+ The problem of oxygen skeleton instability caused by this was solved, and the discharge capacity and long-cycle stability of lithium-ion batteries were improved through the synergistic effect of directional doping strategy and full-structure high-entropy doping strategy.
[0013] In some embodiments, C includes at least one element selected from sodium, magnesium, potassium, and calcium; and D includes at least one element selected from boron, silicon, titanium, chromium, iron, copper, zinc, yttrium, zirconium, niobium, molybdenum, tantalum, tungsten, lanthanum, cerium, neodymium, samarium, terbium, dysprosium, holmium, erbium, ytterbium, and lutetium. And the total number of element types derived from the above C and D doping elements in the positive electrode material is four or more.
[0014] Among the D doping elements, the lanthanide elements have a larger ion radius, can expand the material layer spacing, and have a stronger bonding strength with lattice oxygen than other non-lanthanide elements, thereby further increasing the stability of lattice oxygen.
[0015] In the directional high-entropy doped high-nickel cobalt-free positive electrode material described in the present invention, there may be two C-doping elements and two D-doping elements; or, there may be one C-doping element and three D-doping elements; or, there may be three C-doping elements and one D-doping element.
[0016] The above directional doping schemes can achieve Li + Diffusion is dominant, and the outer region is dominated by lattice stability. However, the present invention finds that when there are two C doping elements and two D doping elements, the performance of the positive electrode material and the battery is better. At this time, the chemical formula of the high nickel cobalt-free positive electrode material is LiNi a B b (C1 c1 C2 c2 )(D1 d1 D2 d2)O2, wherein C1 and C2 are two different C elements, D1 and D2 are two different D elements, cl+c2=c, d1+d2=d, 0.01≤c1≤0.1, 0.01≤c2≤0.1, 0.01≤d1≤0.1, 0.01≤d2≤0.1; c1∶c2∶d1∶d2=1-1.04∶1-1.04∶1-1.04∶1-1.04.
[0017] In some preferred embodiments, 0.01≤c1≤0.03, 0.01≤c2≤0.03, 0.01≤d1≤0.03, 0.01≤d2≤0.03, for example, c1, c2, d1, d2 are independently 0.01, 0.02 or 0.03, and the comprehensive performance of the battery with the doping content within this range is better.
[0018] In some embodiments, the size of the high-nickel cobalt-free positive electrode material is 8 to 12 μm, and the specific surface area is 0.42 to 0.69 m 2 g -1 , tap density is 2.1-2.24 g cm 3 , the shell thickness is 20-500nm.
[0019] The second object of the present invention is to provide a method for preparing a high-nickel cobalt-free positive electrode material with directional high-entropy doping, comprising:
[0020] Annealing a uniform powder containing a nickel source, an aluminum source and / or a manganese source, and a nuclear doping source to obtain a first precursor powder;
[0021] The first precursor powder, the shell doping source, the lithium source and the dispersant are mixed to form a uniform slurry, and the uniform slurry is formed into a second precursor powder by at least an aerosol spray drying method;
[0022] In an oxygen-containing atmosphere, the second precursor powder is subjected to a two-stage sintering treatment to obtain a high-nickel cobalt-free positive electrode material with directional high-entropy doping;
[0023] Among them, the core doping source is used to provide a core doping element C, C is selected from the elements in the first main group and the second main group of the periodic table except Li; the shell doping source is used to provide a shell doping element D, D is selected from the elements in the second to sixth periods of the periodic table except Li, Ni, Mn, Al and C (C here refers to the above-mentioned doping element C rather than carbon), and the total element types of C and D doping elements are more than four, and the molar ratio of any two elements of C and D is 1-1.04:1-1.04.
[0024] The present invention adopts a one-step lithium mixing combined with a spray drying method to prepare a high-nickel cobalt-free positive electrode material, and the obtained material has a uniform particle size distribution and a high sphericity; compared with traditional preparation methods of high-nickel cobalt-free materials (such as coprecipitation, sol-gel method, hydrothermal method, solid phase method, etc.), the spray drying method can prepare a large amount of precursor powder with excellent performance in a short time, which is conducive to shortening working hours and reducing energy consumption; in addition, the spray drying method does not generate waste liquid during the preparation process, is green, environmentally friendly, and pollution-free, and avoids the problem of a large amount of anionic waste liquid generated by traditional coprecipitation.
[0025] In some embodiments, the annealing treatment is performed at a temperature of 350-700°C, preferably 450-600°C.
[0026] In some embodiments, the annealing treatment time is 3-10 hours, preferably 6-8 hours.
[0027] In some embodiments, the conditions of the aerosol spray drying method include: aerosol pressure of 0.02-0.3MPa, preferably 0.1-0.2MPa; inlet air temperature of 90-250°C, preferably 100-180°C; outlet temperature of 80-200°C, preferably 100-150°C; feed rate of 1-50mL / min, preferably 10-20mL / min; induced draft fan frequency of 20-45Hz, preferably 35-40Hz.
[0028] In some embodiments, the temperature of the first stage of the two-stage sintering treatment is 300-600°C, preferably 400-550°C, and the insulation time of the first stage is 4-10h, preferably 6-8h; the temperature of the second stage of the two-stage sintering treatment is 700-900°C, preferably 700-880°C, and the insulation time of the second stage is 10-24h, preferably 12-15h.
[0029] In some embodiments, the oxygen-containing atmosphere includes oxygen, and the flow rate of the oxygen is 60-180 mL / min, preferably 100-120 mL / min.
[0030] In some embodiments, the preparation method specifically includes: ball milling a first mixture containing a nickel source, an aluminum source and / or a manganese source, a nuclear doping source and a solvent to obtain the uniform powder, and the conditions of the ball milling include: a ball milling speed of 200-1200rpm, preferably 400-900rpm, and a ball milling time of 6-24h, preferably 12-16h.
[0031] In some embodiments, the solvent includes one or more of anhydrous ethanol, water, ether, dimethylformamide, ethylene glycol, glycerol, acetone or glycerol. Preferably, the solvent includes anhydrous ethanol and / or water.
[0032] In some embodiments, the preparation method specifically includes: subjecting the second mixture containing the first precursor powder, the shell doping source, the lithium source and the dispersant to high-energy ball milling to form the uniform slurry, and the conditions of the high-energy ball milling include: the high-energy ball milling speed is 600-2000rpm, preferably 900-1200rpm; the high-energy ball milling time is 2-12h, preferably 6-10h; the diameter of the grinding ball is 0.01-2mm, preferably 0.1-1mm; the material of the grinding ball includes but is not limited to zirconium oxide.
[0033] In some embodiments, the core doping source includes at least one of a sodium source, a magnesium source, a potassium source, and a calcium source; the shell doping source includes at least one of a boron source, a silicon source, a titanium source, a chromium source, an iron source, a copper source, a zinc source, a yttrium source, a zirconium source, a niobium source, a molybdenum source, a tantalum source, a tungsten source, a lanthanum source, a cerium source, a neodymium source, a samarium source, a terbium source, a dysprosium source, a holmium source, an erbium source, a ytterbium source, and a lutetium source; and the number of the core doping source and the shell doping source is four or more.
[0034] In some embodiments, there are two types of core doping sources and two types of shell doping sources; or, there is one type of core doping source and three types of shell doping sources; or, there are three types of core doping sources and one type of shell doping source. Preferably, there are two types of core doping sources and two types of shell doping sources.
[0035] In some embodiments, the sodium source includes an organic sodium source and / or an inorganic sodium source, the organic sodium source includes one or more of sodium acetate, sodium polymethacrylate, and sodium biphenyl, and the inorganic sodium source includes one or more of sodium hydroxide, sodium carbonate, sodium sulfate, or sodium oxide. Preferably, the sodium source includes sodium carbonate and / or sodium sulfate.
[0036] In some embodiments, the magnesium source includes an organic magnesium source and / or an inorganic magnesium source, the organic magnesium source includes one or more combinations of magnesium acetate, magnesium tert-butoxide, and dimethyl magnesium, and the inorganic magnesium source includes one or more combinations of magnesium hydroxide, magnesium carbonate, magnesium sulfate, and magnesium oxide. Preferably, the magnesium source includes magnesium carbonate and / or magnesium sulfate.
[0037] In some embodiments, the potassium source includes an organic potassium source and / or an inorganic potassium source, the organic potassium source includes one or more of potassium methoxide, potassium methanesulfonate, and potassium isopropoxide, and the inorganic potassium source includes one or more of potassium hydroxide, potassium carbonate, potassium sulfate, and potassium oxide. Preferably, the potassium source includes potassium carbonate and / or potassium sulfate.
[0038] In some embodiments, the calcium source includes an organic calcium source and / or an inorganic calcium source, the organic calcium source includes one or more of calcium citrate, calcium gluconate, and amino acid calcium, and the inorganic potassium source includes one or more of calcium hydroxide, calcium carbonate, calcium sulfate, and calcium oxide. Preferably, the calcium source includes calcium carbonate and / or calcium sulfate.
[0039] In some embodiments, the shell doping source includes an oxide of the shell doping element, such as boron oxide, silicon oxide, titanium oxide, chromium oxide, iron oxide, copper oxide, zinc oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, tantalum oxide, tungsten oxide, lanthanum oxide, cerium oxide, neodymium oxide, samarium oxide, terbium oxide, dysprosium oxide, holmium oxide, erbium oxide, ytterbium oxide, lutetium oxide, etc.
[0040] In some preferred embodiments, the shell doping source includes one or more of titanium oxide, iron oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, tantalum oxide, tungsten oxide, lanthanum oxide, samarium oxide, holmium oxide, erbium oxide, and lutetium oxide. The shell doping source has a stronger bond with lattice oxygen and can stabilize lattice oxygen during lithium ion insertion and extraction.
[0041] In some embodiments, the amounts of the nickel source, aluminum source and / or manganese source, core doping source, and shell doping source satisfy the following conditions: the molar ratio of nickel, aluminum and / or manganese, core doping element C, and shell doping element D is 0.6-0.99: 0.01-0.4: 0.01-0.2: 0.01-0.2.
[0042] In some embodiments, the dispersant includes one or more combinations of polysodium lauryl sulfate, potassium lauryl sulfate, sodium octylbenzene sulfonate, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, sodium polyacrylate, polyvinyl alcohol, polyacrylamide or polyvinyl ether, but is not limited thereto.
[0043] In some preferred embodiments, the dispersant includes one or a combination of more of sodium polydodecyl sulfate, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, sodium polyacrylate, polyvinyl alcohol or polyacrylamide.
[0044] In some embodiments, the amount of the dispersant used is 0.1-10 wt %, preferably 1-5 wt %, of the total mass of solids in the uniform slurry.
[0045] In some embodiments, the nickel salt includes an organic nickel source and / or an inorganic nickel source, the organic nickel source includes one or more of nickel acetate, nickel phthalocyanine or bis(triphenylphosphine)nickel chloride, and the inorganic nickel source includes nickel hydroxide and / or nickel oxide. Preferably, the nickel source includes nickel hydroxide and / or nickel oxide.
[0046] In some embodiments, the aluminum source includes an organic aluminum source and / or an inorganic aluminum source, the organic aluminum source includes one or more of aluminum acetate, trialkyl aluminum or dialkyl aluminum chloride, and the inorganic aluminum source includes aluminum hydroxide and / or aluminum oxide. Preferably, the aluminum source includes aluminum hydroxide and / or aluminum oxide.
[0047] In some embodiments, the manganese source includes an organic manganese source and / or an inorganic manganese source, the organic manganese source includes one or more of manganese acetate, pentacarbonyl manganese bromide or manganese phthalocyanine, and the inorganic manganese source includes manganese hydroxide and / or manganese oxide. Preferably, the manganese source includes manganese hydroxide and / or manganese oxide.
[0048] In some embodiments, the lithium source includes an organic lithium source and / or an inorganic lithium source, the organic lithium source includes one or more of lithium acetate, n-butyl lithium or phenyl lithium, and the inorganic lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium sulfate or lithium oxide. Preferably, the lithium source includes one or more of lithium carbonate, lithium hydroxide or lithium oxide.
[0049] The third object of the present invention is to provide the use of the high-nickel cobalt-free positive electrode material described in any technical solution or the high-nickel cobalt-free positive electrode material prepared by the method described in any technical solution in the preparation of a lithium-ion battery positive electrode or a lithium-ion battery.
[0050] A fourth object of the present invention is to provide a positive electrode for a lithium-ion battery, comprising a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, characterized in that: the positive electrode active material layer comprises the high-nickel cobalt-free positive electrode material or the high-nickel cobalt-free positive electrode material prepared by the method described.
[0051] A fifth object of the present invention is to provide a lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the positive electrode is the positive electrode for the lithium ion battery.
[0052] Compared with the prior art, the present invention has at least the following beneficial effects:
[0053] (1) The high-nickel cobalt-free positive electrode material provided by the present invention achieves high entropy of the entire structure through element screening and directional doping, solves the dependence of the high-nickel positive electrode on the cobalt element through element substitution, and solves the problems of slow diffusion and low conductivity caused by cobalt deficiency.
[0054] (2) Directed doping in the high entropy region (core) inside the positive electrode with high Li + Diffusion is dominant, and the Li site substitution is achieved in a highly delithiation state. + The "pillar" effect of the diffused two-dimensional crystal surface accelerates the Li + Rapid diffusion inside the positive electrode.
[0055] (3) Through directional doping in the high entropy region (shell) outside the positive electrode, lattice stability is dominant, and Me sites are replaced on the surface and near the surface of the positive electrode, which reduces the Li + The spinel phase and rock salt phase formed by deintercalation; and the highly reactive Ni on the particle surface is solved by strong Me-O bonding. 4+ The resulting oxygen skeleton instability problem improves the discharge capacity and long-cycle stability of lithium-ion batteries.
[0056] (4) Furthermore, the present invention can achieve controllable adjustment of the optimized areas of the inner and outer parts by adjusting the element ratios of the high entropy regions inside and outside the positive electrode. For example, for particles with larger sizes, the element ratio of the internal high entropy region can be increased to accelerate the Li + Diffusion inside the particles; for particles with smaller sizes, the proportion of elements in the external high entropy region can be increased to reduce the interface instability caused by the high specific surface area; further, by evenly dividing the doping elements in the external and internal high entropy regions, the high Li + Diffusion and surface lattice oxygen stability.
[0057] (5) The high-nickel cobalt-free positive electrode material prepared by the one-step lithium mixing combined with spray drying method has uniform particle size distribution and high sphericity; and the method is efficient, rapid, green, environmentally friendly, pollution-free, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0059] Figure 1 This is a SEM image of the directional high-entropy doped high-nickel cobalt-free positive electrode material obtained in Example 1 of the present invention;
[0060] Figure 2 This is an EDS image of the directional high-entropy doped high-nickel cobalt-free positive electrode material obtained in Example 1 of the present invention;
[0061] Figure 3 This is the XRD spectrum of the positive electrode of the high-nickel cobalt-free positive electrode material obtained in Example 1 of the present invention;
[0062] Figure 4 is the capacity-voltage curve of the lithium-ion battery obtained in Example 1 of the present invention;
[0063] Figure 5is the rate performance curve of the lithium ion battery obtained in Example 1 of the present invention;
[0064] Figure 6 This is a high-rate long-cycle performance diagram of the lithium-ion battery obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0065] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.
[0066] The raw materials and reagents used in the embodiments and comparative examples of the present invention are commercially available unless otherwise specified.
[0067] Example 1
[0068] Nickel oxide, manganese oxide, and core layer doping sources potassium chloride and calcium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K:Ca=0.9:0.03:0.01:0.02, and ball-milled at a speed of 400 rpm for 10 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder;
[0069] Weighing shell doping sources tantalum oxide and titanium oxide according to a molar ratio of Ta:Ti=0.02:0.02, and dispersing them in deionized water together with the pretreated powder obtained above, and adding a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Mn+K+Ca+Ta+Ti=1.05:1, and the dispersant is 1wt% polyvinylpyrrolidone; high-energy ball milling the above mixture, using 0.5mm zirconium oxide grinding balls, high-energy ball milling at a speed of 1200rpm for 2h to obtain a uniform slurry;
[0070] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0071] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.9 Mn 0.03K 0.01 Ca 0.02 Ta 0.02 Ti 0.02 O2.
[0072] Figure 1 is a SEM image of the directional high-entropy doped high-nickel cobalt-free positive electrode material obtained in this embodiment; Figure 2 This is an EDS image of the directional high-entropy doped high-nickel cobalt-free positive electrode material obtained in this embodiment; Figure 3 is the XRD spectrum of the high-nickel cobalt-free positive electrode material obtained in this embodiment. The unit cell parameters of the doped high-nickel cobalt-free positive electrode material in this embodiment are
[0073] The high-nickel cobalt-free positive electrode material prepared in this embodiment is used to prepare positive electrode plates and assemble lithium-ion batteries, as follows:
[0074] The obtained high-nickel cobalt-free positive electrode material and conductive carbon black (Super-p) were manually ground and mixed for 30 minutes, and the weight ratio of active material: polyvinylidene fluoride (PVDF): conductive carbon black was 8:1:1. PVDF was dissolved in N-methylpyrrolidone (NMP) to form a polymer solution, and then the ground mixture was added to the solution and stirred for 6 hours to form a uniform slurry. The slurry was evenly coated on aluminum foil, and then dried at 80°C for 1 hour. After the punched sheet was taken out, it was placed in a vacuum drying oven at 120°C for 12 hours to obtain a high-nickel cobalt-free positive electrode sheet, which was placed in a glove box for standby use;
[0075] The high-nickel cobalt-free positive electrode plate and the lithium metal negative electrode were assembled into a half-cell to test the battery performance. Cellgard2500 was used as the battery separator, and a solution was prepared with a volume ratio of ethylene carbonate (EC) to dimethyl carbonate (DMC) = 3:7. LiPF6 was dissolved in the solution at a concentration of 1.2M as the lithium-ion battery electrolyte. After the battery was assembled, it was left to stand for 12 hours before the charge and discharge test began.
[0076] The electrochemical performance test of high-nickel cobalt-free positive electrode materials was carried out in the Blue Electric Battery Test System with a test voltage of 2.7-4.3V; the rate performance test conditions were: charge and discharge 5 times at 0.2 / 0.5 / 1 / 2 / 5 / 10C rates, and then charge and discharge 5 times at 0.2C after 10C; the cycle performance test conditions were: charge and discharge 3 times at 0.2C, and then charge and discharge test was carried out at 1C rate to examine the capacity retention rate.
[0077] Figure 4 is the capacity-voltage curve of the lithium-ion battery obtained in this embodiment; Figure 5 is the rate performance curve of the lithium ion battery obtained in this embodiment; Figure 6This is a high-rate long-cycle performance diagram of the lithium-ion battery obtained in this example.
[0078] Example 2
[0079] Nickel oxide, aluminum oxide, and core layer doping sources magnesium carbonate and sodium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Al:Mg:Na=0.92:0.01:0.02:0.02, and ball-milled at a speed of 1200 rpm for 20 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 500°C for 6 h to obtain a pretreated powder;
[0080] The shell doping sources of iron oxide and tungsten oxide were weighed according to a molar ratio of Fe:W=0.01:0.02, and dispersed in deionized water together with the pretreated powder obtained above, and a lithium source and a dispersant were added to form a mixture, wherein the lithium source was anhydrous lithium hydroxide weighed according to a molar ratio of Li:Ni+Al+Mg+Na+Fe+W=1.05:1, and the dispersant was 5wt% polyvinyl alcohol; the mixture was subjected to high-energy ball milling, using a 0.3mm zirconium oxide ball, and ball milling at a speed of 1500rpm for 2h to obtain a uniform slurry;
[0081] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 150°C, outlet temperature of 120°C, feed rate of 20 mL / min, and induced draft fan frequency of 40 Hz. After the spraying was completed, a precursor powder was obtained;
[0082] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 720°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.92 Al 0.01 Mg 0.02 Na 0.02 Fe 0.01 W 0.02 O2.
[0083] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0084] Example 3
[0085] Nickel oxide, aluminum oxide, and core layer doping sources potassium chloride and sodium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Al:K:Na=0.95:0.01:0.01, and ball-milled at a speed of 600 rpm for 9 hours; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 500°C for 6 hours to obtain a pretreated powder;
[0086] Weigh shell doping sources tantalum oxide and niobium oxide according to a molar ratio of Ta:Nb=0.01:0.01, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Al+K+Na+Ta+Nb=1.05:1, and the dispersant is 2wt% polyethylene ether; high-energy ball milling the above mixture is performed at a speed of 1200rpm for 2h using 0.5mm zirconia grinding balls to obtain a uniform slurry;
[0087] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.15 MPa, inlet temperature of 170°C, outlet temperature of 133°C, feed rate of 14 mL / min, and induced draft fan frequency of 40 Hz. After the spraying was completed, a precursor powder was obtained;
[0088] The precursor powder was first sintered at 500°C for 4 h at an oxygen flow of 60 mL / min, then sintered at 700°C for 15 h at an oxygen flow of 80 mL / min, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.95 Al 0.01 K 0.01 Na 0.01 Ta 0.01 Nb 0.01 O2.
[0089] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0090] Example 4
[0091] Nickel hydroxide, manganese oxide, and core layer doping sources potassium chloride and calcium chloride were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K:Ca=0.85:0.03:0.03, and ball-milled at a speed of 200 rpm for 24 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 600°C for 6 h to obtain a pretreated powder;
[0092] Shell doping source silicon oxide and molybdenum oxide are weighed according to a molar ratio of Si:Mo=0.03:0.03, and dispersed in deionized water together with the pretreated powder obtained above, and a lithium source and a dispersant are added to form a mixture, wherein the lithium source is anhydrous lithium hydroxide weighed according to a molar ratio of Li:Ni+Mn+K+Ca+Si+Mo=1.05:1, and the dispersant is 7wt% polyacrylamide; the above mixture is subjected to high-energy ball milling, using 1mm zirconia grinding balls, and high-energy ball milling at a speed of 1000rpm for 3h to obtain a uniform slurry;
[0093] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.02 MPa, inlet temperature of 200°C, outlet temperature of 150°C, feed rate of 30 mL / min, and induced draft fan frequency of 25 Hz. After the spraying was completed, a precursor powder was obtained;
[0094] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 770°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.85 Mn 0.03 K 0.03 Ca 0.03 Si 0.03 Mo 0.03 O2.
[0095] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0096] Example 5
[0097] Nickel hydroxide, aluminum oxide, and core layer doping sources magnesium chloride and calcium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Al:Mg:Ca=0.8:0.1:0.02:0.02, and ball-milled at a speed of 1200 rpm for 6 hours; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 350°C for 10 hours to obtain a pretreated powder;
[0098] The shell doping sources copper oxide and yttrium oxide are weighed according to a molar ratio of Cu:Y=0.03:0.03, and dispersed in deionized water together with the pretreated powder obtained above, and a lithium source and a dispersant are added to form a mixture, wherein the lithium source is anhydrous lithium hydroxide weighed according to a molar ratio of Li:Ni+Al+Mg+Ca+Cu+Y=1.05:1, and the dispersant is 10wt% sodium carboxymethyl cellulose; the above mixture is subjected to high-energy ball milling, using 0.15mm zirconium oxide grinding balls, and high-energy ball milling at a speed of 600rpm for 12h to obtain a uniform slurry;
[0099] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.3 MPa, inlet temperature of 100 ° C, outlet temperature of 86 ° C, feed rate of 10 mL / min, induced draft fan frequency of 30 Hz, and precursor powder was obtained after the spraying was completed;
[0100] The precursor powder was first sintered at 500°C for 4 h at an oxygen flow of 60 mL / min, then sintered at 790°C for 15 h at an oxygen flow of 80 mL / min, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.8 Al 0.1 Mg 0.02 Ca 0.02 Cu 0.03 Y 0.03 O2.
[0101] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0102] Example 6
[0103] Nickel oxide, manganese oxide, and core layer doping sources magnesium chloride and potassium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:Mg:K=0.75:0.12:0.03:0.02, and ball-milled at a speed of 400 rpm for 15 h; the ball-milled powder was dried and placed in a muffle furnace, and pretreated at 600°C for 4 h to obtain a pretreated powder;
[0104] Tantalum oxide and tungsten oxide as shell doping sources are weighed at a molar ratio of Ta:W=0.04:0.04, and dispersed in deionized water together with the pretreated powder obtained above, and a lithium source and a dispersant are added to form a mixture, wherein the lithium source is anhydrous lithium hydroxide weighed at a molar ratio of Li:Ni+Mn+Mg+K+Ta+W=1.05:1, and the dispersant is 1wt% sodium dodecyl sulfate; the above mixture is subjected to high-energy ball milling, using 0.2mm zirconium oxide grinding balls, and high-energy ball milling at a speed of 1500rpm for 2h to obtain a uniform slurry;
[0105] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.3 MPa, inlet temperature of 100 ° C, outlet temperature of 86 ° C, feed rate of 10 mL / min, induced draft fan frequency of 30 Hz, and precursor powder was obtained after the spraying was completed;
[0106] The precursor powder was first sintered at 500°C for 4 h at an oxygen flow of 60 mL / min, then sintered at 820°C for 15 h at an oxygen flow of 80 mL / min, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.75 Mn 0.12 Mg 0.03 K 0.02 Ta 0.04 W 0.04 O2.
[0107] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0108] Example 7
[0109] Nickel oxide, aluminum oxide, and core layer doping sources magnesium chloride and sodium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:AI:Mg:Na=0.7:0.19:0.03:0.02, and ball-milled at a speed of 300 rpm for 22 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 700°C for 3 h to obtain a pretreated powder;
[0110] Weigh shell doping source silicon oxide and yttrium oxide according to a molar ratio of Si:Y=0.03:0.03, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Al+Mg+Na+Si+Y=1.05:1, and the dispersant is 4wt% polyvinyl alcohol; high-energy ball milling the above mixture, using 0.9mm zirconia grinding balls, high-energy ball milling at a speed of 1700rpm for 2h to obtain a uniform slurry;
[0111] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.02 MPa, inlet temperature of 190°C, outlet temperature of 140°C, feed rate of 15 mL / min, and induced draft fan frequency of 35 Hz. After the spraying was completed, a precursor powder was obtained;
[0112] The precursor powder was first sintered at 500°C with an oxygen flow of 60 mL / min for 4 h, and then sintered at 830°C with an oxygen flow of 80 mL / min for 20 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.7 Al 0.19 Mg 0.03 Na 0.02 Si 0.03 Y 0.03O2.
[0113] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0114] Example 8
[0115] Nickel oxide, manganese oxide, and core layer doping sources potassium chloride and sodium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K:Na=0.6:0.3:0.02:0.02, and ball-milled at a speed of 600 rpm for 15 h; the ball-milled powder was dried and placed in a muffle furnace, and pretreated at 640°C for 5 h to obtain a pretreated powder;
[0116] Weigh shell doping sources tantalum oxide and zirconium oxide according to a molar ratio of Ta:Zr=0.03:0.03, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Mn+K+Na+Ta+Zr=1.05:1, and the dispersant is 3wt% polyvinyl alcohol; high-energy ball milling the above mixture, using 0.5mm zirconium oxide grinding balls, high-energy ball milling at a speed of 1500rpm for 1.5h to obtain a uniform slurry;
[0117] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.15 MPa, inlet temperature of 170°C, outlet temperature of 114°C, feed rate of 15 mL / min, and induced draft fan frequency of 35 Hz. After the spraying was completed, a precursor powder was obtained;
[0118] The precursor powder was first sintered at 500°C with an oxygen flow of 60 mL / min for 4 h, and then sintered at 850°C with an oxygen flow of 80 mL / min for 20 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.6 Mn 0.3 K 0.02 Na 0.02 Ta 0.03 Zr 0.03 O2.
[0119] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0120] Example 9
[0121] Nickel oxide, aluminum oxide, and core layer doping sources potassium chloride and magnesium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Al:K:Mg=0.6:0.3:0.03:0.02, and ball-milled at a speed of 700 rpm for 12 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 500°C for 5 h to obtain a pretreated powder;
[0122] The shell doping sources chromium oxide and zinc oxide are weighed according to a molar ratio of Cr:Zn=0.02:0.03, and are dispersed in deionized water together with the pretreated powder obtained above, and a lithium source and a dispersant are added to form a mixture, wherein the lithium source is anhydrous lithium hydroxide weighed according to a molar ratio of Li:Ni+Al+K+Mg+Cr+Zn=1.05:1, and the dispersant is 2.5wt% polyvinyl alcohol; the above mixture is subjected to high-energy ball milling, using a 0.5mm zirconium oxide grinding ball, and high-energy ball milling at a speed of 1200rpm for 2h to obtain a uniform slurry;
[0123] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.14 MPa, inlet temperature of 150°C, outlet temperature of 105°C, feed rate of 15 mL / min, and induced draft fan frequency of 35 Hz. After the spraying was completed, a precursor powder was obtained;
[0124] The above-mentioned precursor powder was first sintered at 450°C with an oxygen flow of 60 mL / min for 4 h, and then sintered at 850°C with an oxygen flow of 80 mL / min for 22 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.6 Al 0.3 K 0.03 Mg 0.02 Cr 0.02 Zn 0.03 O2.
[0125] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0126] Example 10
[0127] Nickel oxide, manganese oxide, and core layer doping sources calcium chloride and potassium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:Ca:K=0.7:0.2:0.02:0.02, and ball-milled at a speed of 500 rpm for 20 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 700°C for 3 h to obtain a pretreated powder;
[0128] Weigh shell doping sources lanthanum oxide and cerium oxide according to a molar ratio of La:Ce=0.03:0.03, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Mn+Ca+K+La+Ce=1.05:1, and the dispersant is 4wt% polyvinyl alcohol; high-energy ball milling the above mixture is performed at a speed of 1700rpm for 2h using 0.9mm zirconia grinding balls to obtain a uniform slurry;
[0129] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.02 MPa, inlet temperature of 190°C, outlet temperature of 140°C, feed rate of 15 mL / min, and induced draft fan frequency of 35 Hz. After the spraying was completed, a precursor powder was obtained;
[0130] The precursor powder was first sintered at 500°C with an oxygen flow of 60 mL / min for 4 h, and then sintered at 830°C with an oxygen flow of 80 mL / min for 20 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.7 Mn 0.2 Ca 0.02 K 0.02 La 0.03 Ce 0.03 O2.
[0131] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0132] Embodiment 11
[0133] Nickel oxide, manganese oxide, and core layer doping sources magnesium chloride and potassium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Al:Na:Ca=0.75:0.12:0.03:0.02, and ball-milled at a speed of 400 rpm for 15 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 600°C for 4 h to obtain a pretreated powder;
[0134] Tantalum oxide and tungsten oxide as shell doping sources are weighed according to a molar ratio of Nd: Sm = 0.04: 0.04, and dispersed in deionized water together with the pretreated powder obtained above, and a lithium source and a dispersant are added to form a mixture, wherein the lithium source is anhydrous lithium hydroxide weighed according to a molar ratio of Li: Ni+AL+Na+Ca+Nd+Sm=1.05:1, and the dispersant is 1wt% sodium dodecyl sulfate; the above mixture is subjected to high-energy ball milling, using 0.2mm zirconium oxide grinding balls, and high-energy ball milling at a speed of 1500rpm for 2h to obtain a uniform slurry;
[0135] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.3 MPa, inlet temperature of 100 ° C, outlet temperature of 86 ° C, feed rate of 10 mL / min, induced draft fan frequency of 30 Hz, and precursor powder was obtained after the spraying was completed;
[0136] The precursor powder was first sintered at 500°C for 4 h at an oxygen flow of 60 mL / min, then sintered at 820°C for 15 h at an oxygen flow of 80 mL / min, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.75 Al 0.12 Na 0.03 Ca 0.02 Nd 0.04 Sm 0.04 O2.
[0137] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0138] Example 12
[0139] Nickel hydroxide, aluminum oxide, and core layer doping sources magnesium chloride and calcium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:Mg:Na=0.8:0.1:0.02:0.02, and ball-milled at a speed of 1000 rpm for 4 hours; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 350°C for 10 hours to obtain a pretreated powder;
[0140] The shell doping sources copper oxide and yttrium oxide are weighed according to a molar ratio of Tb:Dy=0.03:0.03, and are dispersed in deionized water together with the pretreated powder obtained above, and a lithium source and a dispersant are added to form a mixture, wherein the lithium source is anhydrous lithium hydroxide weighed according to a molar ratio of Li:Ni+Mn+Mg+Na+Tb+Dy=1.05:1, and the dispersant is 10wt% sodium carboxymethyl cellulose; the above mixture is subjected to high-energy ball milling, using 0.15mm zirconium oxide grinding balls, and high-energy ball milling at a speed of 600rpm for 12h to obtain a uniform slurry;
[0141] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.3 MPa, inlet temperature of 100 ° C, outlet temperature of 86 ° C, feed rate of 10 mL / min, induced draft fan frequency of 30 Hz, and precursor powder was obtained after the spraying was completed;
[0142] The precursor powder was first sintered at 500°C for 4 h at an oxygen flow of 60 mL / min, then sintered at 790°C for 15 h at an oxygen flow of 80 mL / min, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.8 Mn 0.1 Mg 0.02 Na 0.02 Tb 0.03 Dy 0.03 O2.
[0143] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0144] Embodiment 13
[0145] Nickel hydroxide, manganese oxide, and core layer doping sources potassium chloride and calcium chloride were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Al:K:Ca=0.85:0.03:0.03, and ball-milled at a speed of 200 rpm for 24 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 600°C for 6 h to obtain a pretreated powder;
[0146] Weigh shell doping source silicon oxide and molybdenum oxide according to a molar ratio of Ho:Er=0.03:0.03, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Al+K+Ca+Ho+Er=1.05:1, and the dispersant is 7wt% polyacrylamide; high-energy ball milling the above mixture, using 1mm zirconia grinding balls, high-energy ball milling at a speed of 1000rpm for 3h to obtain a uniform slurry;
[0147] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.02 MPa, inlet temperature of 200°C, outlet temperature of 150°C, feed rate of 30 mL / min, and induced draft fan frequency of 25 Hz. After the spraying was completed, a precursor powder was obtained;
[0148] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 770°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.85 Al 0.03 K 0.03 Ca 0.03 Ho 0.03 Er 0.03 O2.
[0149] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0150] Embodiment 14
[0151] Nickel oxide, aluminum oxide, and core layer doping sources potassium chloride and sodium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:Na:Ca=0.95:0.01:0.01, and ball-milled at a speed of 600 rpm for 9 hours; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 500°C for 6 hours to obtain a pretreated powder;
[0152] Weighing shell doping sources tantalum oxide and niobium oxide according to a molar ratio of Yb:Lu=0.01:0.01, and dispersing them in deionized water together with the pretreated powder obtained above, and adding a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Mn+Na+Ca+Yb+Lu=1.05:1, and the dispersant is 2wt% polyethylene ether; high-energy ball milling the above mixture, using 0.5mm zirconia grinding balls, high-energy ball milling at a speed of 1200rpm for 2h to obtain a uniform slurry;
[0153] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.15 MPa, inlet temperature of 170°C, outlet temperature of 133°C, feed rate of 14 mL / min, and induced draft fan frequency of 40 Hz. After the spraying was completed, a precursor powder was obtained;
[0154] The precursor powder was first sintered at 500°C for 4 h at an oxygen flow of 60 mL / min, then sintered at 700°C for 15 h at an oxygen flow of 80 mL / min, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.95 Mn 0.01 Na 0.01 Ca 0.01 Yb 0.01 Lu 0.01 O2.
[0155] Embodiment 15
[0156] Nickel oxide, manganese oxide, and core layer doping sources potassium chloride and calcium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K:Ca=0.6:0.01:0.0975:0.0975, and ball-milled at a speed of 400 rpm for 10 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder;
[0157] Weigh shell doping sources tantalum oxide and titanium oxide according to a molar ratio of Ta:Ti=0.0975:0.0975, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Mn+K+Ca+Ta+Ti=1.05:1, and the dispersant is 1wt% polyvinylpyrrolidone; high-energy ball milling the above mixture is performed at a speed of 1200rpm for 2h using 0.5mm zirconia grinding balls to obtain a uniform slurry;
[0158] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0159] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.6 Mn 0.01 K 0.0975 Ca 0.0975 Ta 0.0975 Ti 0.0975 O2.
[0160] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0161] Example 16
[0162] Nickel oxide, manganese oxide, and core layer doping sources potassium chloride and calcium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K:Ca=0.77:0.03:0.05:0.05, and ball-milled at a speed of 400 rpm for 10 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder;
[0163] Weigh shell doping sources tantalum oxide and titanium oxide according to a molar ratio of Ta:Ti=0.05:0.05, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Mn+K+Ca+Ta+Ti=1.05:1, and the dispersant is 1wt% polyvinyl pyrrolidone; high-energy ball milling the above mixture is performed at a speed of 1200rpm for 2h using 0.5mm zirconia grinding balls to obtain a uniform slurry;
[0164] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0165] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.77 Mn 0.03 K 0.0s Ca 0.0s Ta 0.05 Ti 0.05 O2.
[0166] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0167] Embodiment 17
[0168] Nickel oxide, manganese oxide, and core layer doping sources potassium chloride and calcium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K:Ca=0.65:0.03:0.08:0.08, and ball-milled at a speed of 400 rpm for 10 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder;
[0169] Weigh shell doping sources tantalum oxide and titanium oxide according to a molar ratio of Ta:Ti=0.08:0.08, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Mn+K+Ca+Ta+Ti=1.05:1, and the dispersant is 1wt% polyvinyl pyrrolidone; high-energy ball milling the above mixture is performed at a speed of 1200rpm for 2h using 0.5mm zirconia grinding balls to obtain a uniform slurry;
[0170] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0171] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.65 Mn 0.03 K 0.08 Ca 0.08 Ta 0.08 Ti 0.08 O2.
[0172] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0173] Embodiment 18
[0174] Nickel oxide, manganese oxide, and core layer doping sources potassium carbonate, calcium sulfate, and sodium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K:Ca:Na=0.90:0.03:0.01:0.02:0.02, and ball-milled at a speed of 1200 rpm for 20 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 500°C for 6 h to obtain a pretreated powder;
[0175] Weighing a shell doping source titanium oxide according to Ti=0.02 mole, and dispersing it in deionized water together with the pretreated powder obtained above, and adding a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li: Ni+Mn+K+Ca+Na+Ti=1.05:1, and the dispersant is 5wt% polyvinyl alcohol; high-energy ball milling is performed on the above mixture, using a 0.3mm zirconium oxide ball, and ball milling at a speed of 1500rpm for 2h to obtain a uniform slurry;
[0176] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 150°C, outlet temperature of 120°C, feed rate of 20 mL / min, and induced draft fan frequency of 40 Hz. After the spraying was completed, a precursor powder was obtained;
[0177] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 720°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.9 Mn 0.03 K 0.01 Ca 0.02 Na 0.02 Ti 0.02 O2.
[0178] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0179] Embodiment 19
[0180] Nickel oxide, manganese oxide, and core layer doping sources potassium carbonate, calcium sulfate, and sodium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K=0.90:0.01:0.02, and ball-milled at a speed of 1200 rpm for 20 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 500°C for 6 h to obtain a pretreated powder;
[0181] Weigh shell doping sources of molybdenum oxide, tantalum oxide and titanium oxide according to a molar ratio of Mo: Ta: Ti = 0.02: 0.02: 0.02, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li: Ni+Mn+K+Ca+Na+Ti=1.05:1, and the dispersant is 5wt% polyvinyl alcohol; high-energy ball milling is performed on the above mixture, using a 0.3mm zirconia ball, and ball milling at a speed of 1500rpm for 2h to obtain a uniform slurry;
[0182] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 150°C, outlet temperature of 120°C, feed rate of 20 mL / min, and induced draft fan frequency of 40 Hz. After the spraying was completed, a precursor powder was obtained;
[0183] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 720°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.9 Mn 0.03 K 0.01 Mo 0.02 Ta 0.02 Ti 0.02 O2.
[0184] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0185] Comparative Example 1
[0186] Nickel oxide, manganese oxide, and core layer doping sources potassium chloride and calcium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K:Ca=0.9:0.07:0.01:0.02, and ball-milled at a speed of 400 rpm for 10 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder;
[0187] The pretreated powder is dispersed in deionized water, and a lithium source and a dispersant are added, wherein the lithium source is anhydrous lithium hydroxide weighed according to a molar ratio of Li: Ni+Mn+K+Ca=1.05:1, and the dispersant is 1wt% polyvinyl pyrrolidone; the above mixture is subjected to high-energy ball milling, using 0.5mm zirconium oxide grinding balls, and high-energy ball milling at a speed of 1200rpm for 2h to obtain a uniform slurry;
[0188] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0189] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi0.9 Mn 0.07 K 0.01 Ca 0.02 O2.
[0190] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this comparative example was used to prepare positive electrode plates, assemble lithium-ion batteries and conduct tests.
[0191] Comparative Example 2
[0192] Nickel oxide and manganese oxide were weighed and dispersed in anhydrous ethanol at a molar ratio of Ni:Mn=0.9:0.06, and the ball milling speed was 400 rpm for 10 h. The ball milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder.
[0193] Weigh shell doping sources of tantalum oxide and titanium oxide according to Ta:Ti=0.02:0.02, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to the molar ratio of Li:Ni+Mn+Ta+Ti=1.05:1, and the dispersant is 1wt% polyvinyl pyrrolidone; high-energy ball milling the above mixture is performed at a speed of 1200rpm for 2h using 0.5mm zirconia grinding balls to obtain a uniform slurry;
[0194] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0195] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.9 Mn 0.06 Ta 0.02 Ti 0.02 O2.
[0196] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this comparative example was used to prepare positive electrode plates, assemble lithium-ion batteries and conduct tests.
[0197] Comparative Example 3
[0198] According to the ratio of Ni=1 mol, nickel oxide was weighed and dispersed in anhydrous ethanol and ball-milled at a speed of 400 rpm for 10 h. The ball-milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder.
[0199] The pretreated powder is dispersed in deionized water, and a lithium source and a dispersant are added to form a mixture, wherein the lithium source is anhydrous lithium hydroxide weighed according to a molar ratio of Li:Ni=1.05:1, and the dispersant is 1wt% polyvinyl pyrrolidone; the mixture is subjected to high-energy ball milling, using 0.5mm zirconium oxide grinding balls, and high-energy ball milling at a speed of 1200rpm for 2h to obtain a uniform slurry;
[0200] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0201] The above-mentioned precursor powder was first sintered at 500°C with an oxygen flow of 60 mL / min for 4 hours, and then sintered at 760°C with an oxygen flow of 80 mL / min for 15 hours, cooled to room temperature, and then ground and sieved to obtain a matrix ternary positive electrode material with the chemical formula LiNiO2.
[0202] The preparation of high-nickel cobalt-free positive electrode plates, battery assembly and testing parameters are the same as in Example 1.
[0203] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this comparative example was used to prepare positive electrode plates, assemble lithium-ion batteries and conduct tests.
[0204] Comparative Example 4
[0205] Nickel oxide and manganese oxide were weighed and dispersed in anhydrous ethanol at a molar ratio of Ni:Mn=0.9:0.1, and the ball milling speed was 400 rpm for 10 h. The ball milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder.
[0206] The pretreated powder is dispersed in deionized water, and a lithium source and a dispersant are added to form a mixture, wherein the lithium source is anhydrous lithium hydroxide weighed according to a molar ratio of Li: Ni + Mn = 1.05: 1, and the dispersant is 1wt% polyvinyl pyrrolidone; the mixture is subjected to high-energy ball milling, using 0.5mm zirconium oxide grinding balls, and high-energy ball milling at a speed of 1200rpm for 2h to obtain a uniform slurry;
[0207] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0208] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.9 Mn 0.1 O2.
[0209] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this comparative example was used to prepare positive electrode plates, assemble lithium-ion batteries and conduct tests.
[0210] The unit cell parameters of the high nickel cobalt-free cathode material of Comparative Example 4 are
[0211] Comparative Example 5
[0212] Nickel oxide, manganese oxide, core layer doping source tantalum oxide and titanium sulfate were weighed and dispersed in anhydrous ethanol according to the molar ratio of Ni:Mn:Ta:Ti=0.9:0.03:0.01:0.02, and the ball milling was performed at a speed of 400 rpm for 10 hours. The ball milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 hours to obtain a pretreated powder.
[0213] Weighing shell doping sources potassium chloride and titanium sulfate according to a molar ratio of K:Ca=0.02:0.02, and dispersing them in deionized water together with the pretreated powder obtained above, and adding a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Mn+Ta+Ti+K+Ca+=1.05:1, and the dispersant is 1wt% polyvinylpyrrolidone; high-energy ball milling the above mixture, using 0.5mm zirconia grinding balls, high-energy ball milling at a speed of 1200rpm for 2h to obtain a uniform slurry;
[0214] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0215] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.9 Mn 0.03 Ta 0.01 Ti 0.02 K 0.02 Ca 0.02 O2.
[0216] Comparative Example 6
[0217] Nickel oxide, aluminum oxide, and core layer doping sources iron oxide and tungsten oxide were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Al:Fe:W=0.92:0.01:0.02:0.02, and ball-milled at a speed of 1200 rpm for 20 h; the ball-milled powder was dried and placed in a muffle furnace for pretreatment at 500°C for 6 h to obtain a pretreated powder;
[0218] Weigh shell doping sources magnesium carbonate and sodium sulfate according to a molar ratio of Mg:Na=0.01:0.02, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Al+Fe+W+Mg+Na=1.05:1, and the dispersant is 5wt% polyvinyl alcohol; high-energy ball milling is performed on the above mixture, using a 0.3mm zirconia ball, and ball milling at a speed of 1500rpm for 2h to obtain a uniform slurry;
[0219] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 150°C, outlet temperature of 120°C, feed rate of 20 mL / min, and induced draft fan frequency of 40 Hz. After the spraying was completed, a precursor powder was obtained;
[0220] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 720°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.92 Al 0.01 Fe 0.02 W 0.02 Mg 0.01 Na 0.02 O2.
[0221] In the same manner as in Example 1, the high-nickel cobalt-free positive electrode material prepared in this example was used to prepare positive electrode plates, assemble lithium-ion batteries, and conduct tests.
[0222] Comparative Example 7
[0223] Nickel oxide, manganese oxide and core layer doping source potassium chloride were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K=0.9:0.03:0.03, and the ball milling was performed at a speed of 400 rpm for 10 h. The ball milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder.
[0224] The shell doping source tantalum oxide is weighed according to Ta=0.04 mole, and is dispersed in deionized water together with the pretreated powder obtained above, and a lithium source and a dispersant are added to form a mixture, wherein the lithium source is anhydrous lithium hydroxide weighed according to the molar ratio of Li: Ni+Mn+K+Ta=1.05:1, and the dispersant is 1wt% polyvinyl pyrrolidone; the above mixture is subjected to high-energy ball milling, using 0.5mm zirconium oxide grinding balls, and high-energy ball milling at a speed of 1200rpm for 2h to obtain a uniform slurry;
[0225] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0226] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.9 Mn 0.03 K 0.03 Ta 0.04 O2.
[0227] Comparative Example 8
[0228] Nickel oxide, manganese oxide, and core layer doping sources potassium chloride and calcium sulfate were weighed and dispersed in anhydrous ethanol according to a molar ratio of Ni:Mn:K:Ca:Ta:Ti=0.9:0.03:0.00875:0.00875:0.00875:0.00875, and ball-milled at a speed of 400 rpm for 10 h. The ball-milled powder was dried and placed in a muffle furnace for pretreatment at 450°C for 6 h to obtain a pretreated powder.
[0229] Weigh shell doping sources tantalum oxide and titanium oxide according to a molar ratio of K:Ca:Ta:Ti=0.00875:0.00875:0.00875:0.00875, and disperse them in deionized water together with the pretreated powder obtained above, and add a lithium source and a dispersant to form a mixture, wherein the lithium source is anhydrous lithium hydroxide according to a molar ratio of Li:Ni+Mn+K+Ca+Ta+Ti=1.05:1, and the dispersant is 1wt% polyvinylpyrrolidone; high-energy ball milling the above mixture is performed at a speed of 1200rpm for 2h using 0.5mm zirconia grinding balls to obtain a uniform slurry;
[0230] The uniform slurry obtained above was pumped into a spray dryer, and the spray parameters were adjusted as follows: aerosol pressure of 0.2 MPa, inlet temperature of 200°C, outlet temperature of 142°C, feed rate of 10 mL / min, and induced draft fan frequency of 45 Hz. After the spraying was completed, a precursor powder was obtained;
[0231] The above-mentioned precursor powder was first sintered at 500°C and an oxygen flow of 60 mL / min for 4 h, and then sintered at 760°C and an oxygen flow of 80 mL / min for 15 h, cooled to room temperature, and then ground and sieved to obtain a directional high-entropy doped high-nickel cobalt-free cathode material with a chemical formula of LiNi 0.9 Mn 0.03 K 0.0175 Ca 0.0175 Ta 0.0175 Ti 0.0175 O2.
[0232] Table 1 The content ratio of each element in the high nickel cobalt-free positive electrode materials in the embodiments of the present invention and the comparative examples
[0233]
[0234]
[0235] Table 2 Performance of lithium-ion batteries obtained in the embodiments of the present invention and comparative examples
[0236]
[0237]
[0238] In summary, the present invention proposes a directional high-entropy doped lithium-ion battery high-nickel cobalt-free positive electrode material and a preparation method thereof. By selecting elements and adjusting the properties of the spray slurry, a lithium-containing precursor is prepared by spray drying, and a high-Li internal cathode material can be prepared by sintering once. +Diffusion rate, high entropy doped high nickel cobalt-free cathode material with high surface lattice stability. The cathode material first has four core effects (high entropy effect, lattice distortion effect, slow diffusion effect and cocktail effect) due to high entropy doping, which makes the cathode material have good stability and heat resistance; secondly, due to the directional screening of elements, the high entropy area inside the particles is high Li + Diffusion is dominant, while the external high entropy region is dominated by lattice stability, that is, the Li + Slow diffusion and highly reactive Ni on particle surface 4+ The problem of unstable oxygen skeleton is caused by high entropy doping. While enhancing the electrochemical performance, the pain points of cobalt-free positive electrode are solved in a targeted manner, achieving high nickel cobalt-free positive electrode materials with high discharge specific capacity and long cycle stability.
[0239] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0240] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0241] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.
Claims
1. A directional high-entropy doped high-nickel cobalt-free positive electrode material, characterized in that: The directional high entropy doped high nickel cobalt-free positive electrode material comprises a core and a shell layer covering the core, and the chemical formula of the high nickel cobalt-free positive electrode material is LiNi a B b C c D d O2, 0.6≤a≤0.99, 0.01≤b≤0.4, 0.01≤c≤0.2, 0.01≤d≤0.2, a+b+c+d=1; Wherein, B includes at least one element of manganese and aluminum; C is a doping element distributed in the core, the C element replaces part of the Li site of the core of the positive electrode material, and is selected from at least one element of sodium, magnesium, potassium, and calcium; D is a doping element distributed in the shell, the D element replaces part of the Me site of the shell of the positive electrode material, and is selected from at least one element of boron, silicon, titanium, chromium, iron, copper, zinc, yttrium, zirconium, niobium, molybdenum, tantalum, tungsten, lanthanum, cerium, neodymium, samarium, terbium, dysprosium, holmium, erbium, ytterbium, and lutetium; the total number of element types of C and D doping elements in the directional high-entropy doped high-nickel cobalt-free positive electrode material is more than four, and the molar ratio of any two elements of C and D is 1-1.04:1-1.04; In addition, the preparation method of the directional high-entropy doped high-nickel cobalt-free positive electrode material includes: annealing a uniform powder containing a nickel source, an aluminum source and / or a manganese source, and a core doping source to obtain a first precursor powder; mixing the first precursor powder, a shell doping source, a lithium source and a dispersant to form a uniform slurry, and at least using an aerosol spray drying method to make the uniform slurry form a second precursor powder; in an oxygen-containing atmosphere, performing a two-stage sintering treatment on the second precursor powder to obtain a directional high-entropy doped high-nickel cobalt-free positive electrode material; the core doping source is used to provide a core doping element C, and the shell doping source is used to provide a shell doping element D.
2. The directional high-entropy doped high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: The directional high entropy doped high nickel cobalt-free positive electrode material has two C doping elements and two D doping elements; Alternatively, the C doping element is one and the D doping elements are three; Alternatively, the number of C doping elements is three and the number of D doping element is one.
3. The directional high-entropy doped high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: The number of C doping elements is two and the number of D doping elements is two.
4. The directional high entropy doped high nickel cobalt-free positive electrode material according to claim 1, characterized in that: The core doping source is selected from at least one of a sodium source, a magnesium source, a potassium source, and a calcium source; the shell doping source is selected from at least one of a boron source, a silicon source, a titanium source, a chromium source, an iron source, a copper source, a zinc source, a yttrium source, a zirconium source, a niobium source, a molybdenum source, a tantalum source, a tungsten source, a lanthanum source, a cerium source, a neodymium source, a samarium source, a terbium source, a dysprosium source, a holmium source, a erbium source, a ytterbium source, and a lutetium source.
5. The directional high-entropy doped high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: The annealing treatment temperature is 350-700° C.; and / or the annealing treatment time is 3-10 hours.
6. The directional high-entropy doped high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: The conditions of the aerosol spray drying method include: aerosol pressure of 0.02-0.3MPa, air inlet temperature of 90-250°C, outlet temperature of 80-200°C, feed rate of 1-50mL / min, and induced draft fan frequency of 20-45Hz.
7. The directional high-entropy doped high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: The temperature of the first stage of the two-stage sintering process is 300-600°C, and the insulation time of the first stage is 4-10h; the temperature of the second stage of the two-stage sintering process is 700-900°C, and the insulation time of the second stage is 10-24h.
8. The directional high entropy doped high nickel cobalt-free positive electrode material according to claim 1, characterized in that: The preparation method specifically includes: ball milling a first mixture containing a nickel source, an aluminum source and / or a manganese source, a nuclear doping source and a solvent to obtain the uniform powder, and the conditions of the ball milling include: a ball milling speed of 200-1200rpm and a time of 6-24h.
9. The directional high entropy doped high nickel cobalt-free positive electrode material according to claim 1, characterized in that: The preparation method specifically includes: subjecting the second mixture containing the first precursor powder, shell doping source, lithium source and dispersant to high-energy ball milling to form the uniform slurry, and the conditions of the high-energy ball milling include: the high-energy ball milling speed is 600-2000rpm, the time is 2-12h, the diameter of the grinding balls used is 0.01-2mm, and the material of the grinding balls used includes zirconium oxide.
10. The directional high-entropy doped high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: There are two types of core doping sources and two types of shell doping sources; or, there is one type of core doping source and three types of shell doping sources; or, there are three types of core doping sources and one type of shell doping source.
11. The directional high entropy doped high nickel cobalt-free positive electrode material according to claim 1, characterized in that: The amounts of the nickel source, aluminum source and / or manganese source, core doping source and shell doping source are such that the molar ratio of nickel, aluminum and / or manganese, core doping element C and shell doping element D is 0.6-0.99: 0.01-0.4: 0.01-0.2: 0.01-0.
2.
12. The directional high-entropy doped high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: The dispersant includes one or more combinations of polysodium lauryl sulfate, potassium lauryl sulfate, sodium octylbenzene sulfonate, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, sodium polyacrylate, polyvinyl alcohol, polyacrylamide or polyvinyl ether.
13. The directional high-entropy doped high-nickel cobalt-free positive electrode material according to claim 1, characterized in that: The amount of the dispersant used is 0.1-10 wt % of the total solid mass in the uniform slurry.
14. Use of the directional high entropy doped high nickel cobalt-free positive electrode material according to any one of claims 1 to 13 in the preparation of a lithium ion battery positive electrode or a lithium ion battery.
15. A positive electrode for a lithium ion battery, comprising a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, characterized in that: The positive electrode active material layer comprises the directional high-entropy doped high-nickel cobalt-free positive electrode material according to any one of claims 1 to 13.
16. A lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The positive electrode is the positive electrode for a lithium ion battery according to claim 15 .
Citation Information
Patent Citations
Nickel-based positive electrode material with entropy gradient and preparation method thereof
CN116632186A
High-entropy alloy modified high-nickel cobalt-free positive electrode material and preparation method thereof
CN117059795A
Modified cobalt-free and lithium-rich positive electrode material as well as preparation method and application thereof
CN113782748A
High-rate positive electrode material, preparation method thereof and lithium ion battery
CN115557545A
High-entropy nickel-rich cobalt-free core-shell structure positive electrode material as well as preparation method and application thereof
CN118198318A